Theory of critical reading by Fabio Jury applied to students of the text comprehension and interpretation course at the University of Pamplona Cúcuta - Norte de Santander (Revista Investigación & praxis en CS Sociales, 2024)
This article analyzes the application of Fabio Jurado's critical reading theory in university students taking a text comprehension and interpretation course. Using a qualitative approach with an action research, documentary, and field design, students and professors from the Humanities and Spanish Language program were studied. Interviews and diagnostic tests were used to gather information. The results show that critical reading, according to Jurado, is an active, participatory, and reflective process that involves understanding, analyzing, and evaluating a text. The importance of this skill is highlighted for university students to be able to understand reading materials and develop their critical thinking. The research confirms the three levels of reading proposed by Jurado: literal, inferential, and critical, each with its specific characteristics for textual comprehension and interpretation. This study contributes to the understanding of critical reading in higher education and offers tools for its application in the classroom.
Keywords: Critical reading; reading comprehension; text interpretation; higher education; critical thinking